PH-dependent roles of polycarboxylates in electron transfer between Cr(VI) and weak electron donors. (April 2018) - Jiang, Bo; He, Haihong; Liu, Yijie; Tang, Yizhen; Luo, Siyi; Wang, Zhaohui
Abstract: This study reports that the redox reactions between weak electron donors and Cr(VI) can be significantly accelerated by many environmentally occurring or industrially produced polycarboxylates (PolyCAs). The results demonstrate that oxalic acid (OA) can act as a redox mediator to accelerate the reduction of Cr(VI) by As(III) in pH range of 2.0–5.0, as well as a reductant donating electron for Cr(VI) reduction at pH < 4.0. Density functional theory calculation results indicate that the coordination of OA with Cr(VI) can remarkably enhance the reactivity of the CrO bond in HCrO4 − toward oxygen atom transfer or the protonation of oxo groups during Cr(VI) reduction. Moreover, the ligand field effect can also cause instability in the tetrahedral Cr(VI) species, which probably lowers the reaction barrier in the transformation of tetrahedral Cr(VI) to octahedral Cr(III), and therefore favors the reduction of Cr(VI) to Cr(III). Similar to OA, other aliphatic and amino PolyCAs can also accelerate the reduction of Cr(VI), which depends significantly on both the electron transfer capabilities of PolyCAs and their abilities to coordinate chromium species. In general, our findings indicate the novel effect of the interplay between PolyCAs and chromium species on Cr(VI) reduction and provide significant information to develop remediation strategies for Cr(VI) contamination. Graphical abstract: Image 1 Highlights: PolyCAs can facilitate the electron transfer between Cr(VI) and weak electron donors. PolyCAs act as redox mediators and electron donors to accelerate Cr(VI) reduction. The affinity of PolyCAs to Cr(VI) is prerequisite to enhancing Cr(VI) reduction. The mediating roles of PolyCAs in Cr(VI) reduction is negatively affect by increasing solution pH. The mediating roles of PolyCAs are significant under environmental and industrial conditions.